Exploring the occupational therapist's role in primary health care: Listening to voices of stakeholders - Deshini Naidoo; Jacqueline Van Wyk; Robin W. E. Joubert (AOSIS, 2016)
Background: Re-engineering of primary healthcare (PHC) was initiated nationally in 2009. There is, however, little information on the role expected of occupational therapists (OTs)in PHC. Objectives: This research aimed to understand how stakeholders of the Department of Health (DOH) perceived the role of OT in PHC service. Method: This exploratory, qualitative study used purposive sampling to recruit community health-care workers (CHW; n = 23), primary healthcare nurses (PHC; n = 5), DOH management (n = 5), experienced (n = 14) and novice OTs (n = 37) who graduated from the University of KwaZulu-Natal. The PHC nurses and the CHW represented PHC clinics in one district in KwaZulu-Natal. Data were collected through semi-structured interviews and focus groups. Interviews with CHWs were conducted in isiZulu. These were transcribed and translated prior to data analysis. Audio recordings of English interviews and focus groups were transcribed. Data for each participant group were inductively and thematically analysed to identify the themes. Results: The findings provided an indication of the role of OTs in PHC settings. All participants perceived the role of OTs as predominantly curative/rehabilitation-based and individualised. Participants had a limited understanding of the key principles of PHC. They identified a need for adult and paediatric rehabilitation and early childhood intervention. Limited mention was made of population-based approaches, collaborative, and health promotion and prevention programmes. Conclusion: The study has highlighted that neither management nor OTs seemed to align practice and planning according to PHC principles. A review of the theory and experiential learning in the OT programme is required.